Diffusive–Dispersive and Reactive Fronts in Porous Media: Iron(II) Oxidation at the Unsaturated–Saturated Interface. Issue 5 (1st July 2015) - Haberer, Christina M.; Muniruzzaman, Muhammad; Grathwohl, Peter; Rolle, Massimo
Abstract : Diffusive–dispersive mass transfer is important for many groundwater quality problems as it drives the interaction between different reactants, thus influencing a wide variety of biogeochemical processes. In this study, we performed laboratory experiments to quantify O2 transport in porous media, across the unsaturated–saturated interface, under both conservative and reactive transport conditions. As reactive system we considered the abiotic oxidation of Fe 2+ in the presence of O2 . We studied the reaction kinetics in batch experiments and its coupling with diffusive and dispersive transport processes by means of one‐dimensional columns and two‐dimensional flow‐through experiments, respectively. A noninvasive optode technique was used to track O2 transport into the initially anoxic porous medium at highly resolved spatial and temporal scales. The results show significant differences in the propagation of the conservative and reactive O2 fronts. Under reactive conditions, O2, continuously provided from the atmosphere, was considerably retarded due to the interaction with dissolved Fe(II), initially present in the anoxic groundwater. The reaction between dissolved O2 and Fe 2+ led to the formation of an Fe(III) precipitation zone in the experiments. Reactive transport modeling based on a kinetic PHREEQC module tested in controlled batch experiments allowed a quantitative interpretation of the experimental results in both one‐ and two‐dimensional setups.